PATIENT PERCEPTION TOWARDS ARTIFICIAL INTELLIGENCE IN HEALTHCARE: TRUST, ACCEPTANCE, AND ETHICAL - Garima Pathania; Dr. Ashok Bansal (IJRDO - Journal of Business Management, 2026)
Artificial intelligence (AI) is becoming a regularly used component in healthcare models around the globe and transforming the processes of clinical decision-making, diagnostics, patient monitoring, and administration. Regardless of the rapid development of technology, the introduction of AI into the healthcare industry is highly dependent on patients, their views and trust. The current paper is a review of the literature and a synthesis of the existing empirical data related to the subject of patient perception of AI in the medical facility. Based on the researches made with various demographic groups and in different health settings, the paper will explore determinants that promote patient acceptance or resistance such as transparency, explainability, cultural sensitivity, existing knowledge of technology, and privacy and data security concerns. The analysis also discusses how patient autonomy and algorithmic decision-making interact, how the collaboration between physicians and AI affects patient trust, and how healthcare organizations can act ethically concerning the responsible implementation of AI. The results show that although patients recognize the opportunities of AI to enhance the process of healthcare delivery, the lack of trust, insufficient health literacy, and dehumanization fears do not allow the widespread acceptance of AI. Implications on healthcare policy, the design of human-centered AI systems, and recommendations on improving patient engagement in AI transition are presented at the end of the paper.